Time evolution of the growth of single graphene crystals and high resolution isotope labeling. (January 2017) - Whiteway, Eric; Yang, Wayne; Yu, Victor; Hilke, Michael
Abstract: We developed a method of precise isotope labeling to visualize the continuous growth of graphene by chemical vapour deposition (CVD). This method allows us to observe, as a function of time, the growth of graphene monocrystals at a resolution of a few seconds. This technique is used to extract the anisotropic growth rates, as well as investigate the formation of dendrites, and the dependence of growth rate on adsorption area of methane on copper. This technique also gives precise start times for individual graphene nucleation sites. We obtain a physical picture of the growth dynamics of graphene and its dependence on various parameters. Finally, our method is relevant to other CVD grown materials.